Movement and nesting ecology of two endangered Hawaiian waterbirds - Roerk, Lisa, author; Wells, Caitlin, advisor; Tulanowski, Elizabeth, committee member; Pejchar, Liba, committee member (Colorado State University. Libraries, 2025)
Waterbirds rely on the preservation of wetland habitats to support key life-history cycles. Emerging threats to wetland habitats from climate change include increased variability in precipitation, salinity intrusion, and sea level rise; these changes can exacerbate wetland drying and flooding periods and erode the extent and quality of coastal wetlands, making it more difficult for waterbirds to find suitable habitat across their annual cycle. Hawaii's waterbirds are especially at risk, as the island of O'ahu has already lost 65% of its wetlands to development. Before remaining habitat is lost to sea level rise changes to water availability can affect water quality, food abundance, and plant communities for Hawaii's waterbirds. The Hawaiian Common Gallinule ('alae 'ula, Gallinula galeata sandvicensis) and the Hawaiian Coot ('alae ke'oke'o, Fulica alai) are the only two Hawaiian Rallid endemics found in the world, both endangered and conservation-reliant. However, there is limited information on how Hawaiian coots and gallinules may respond to changing environmental conditions of water availability, either through movement or nesting habitat selection. I tracked population and individual movements through waterbird surveys and satellite GPS transmitters from January of 2023 to April of 2025 at Kailua, HI, USA, and evaluated the effects of water availability and quality on abundance, space use, and documented the timing of long-distance movements. I also determined habitat characteristics affecting nest site selection and hatching success of the Hawaiian gallinule. Hawaiian coots had a higher propensity to movement perhaps linked to seasonal changes in environmental conditions, while Hawaiian gallinules remained sedentary despite fluctuations in water availability. I found synchronous changes in the abundance of Hawaiian coots at three wetland sites in Kailua, HI, indicating immigration from wetlands outside the local area and seasonality in abundance with increases in the wet season. Hawaiian coot abundance was affected by water level, rainfall, and water quality, suggesting coots were moving to find favorable habitat. In contrast, gallinule abundance was not impacted by water-related variables; rather, declines in abundance may have been from golf course hazards. Through, satellite GPS transmitter tracking, 24% of coots and 10% of gallinules tracked moved away from their home wetland, but individual movements did not appear seasonal. Both Hawaiian coots and gallinules had similar home range sizes during the wet and dry seasons, and little effects of sex, and site on Hawaiian coot home range, and no effects on Hawaiian gallinule home range. Nesting success of Hawaiian gallinules was high (83%), likely due to the absence of predators at the nest and flooding events. Failures were attributed to conspecific egg destruction, abandonment, and unknown causes. Hatching success averaged 53.4% and increased with water depth nearest the nest; deeper water can provide abundant invertebrate food sources, thus reducing time off the nest, resulting in consistent incubation and nest protection. I found that native vegetation around the nest was the only nest-site characteristic significantly associated with nest-site selection in a landscape dominated by non-native pickleweed (Batis maritima). My results show that Hawaiian coots have a higher propensity to movement than gallinules, and water availability influences successful nesting of gallinules. Management of nesting habitat where sedentary Hawaiian gallinules occur may increase population productivity, and preservation of landscape-wetland habitat connectivity may aid Hawaiian coots in safe passage in local and regional movements. As sea level rise and climate change increase freshwater scarcity and degrade wetland habitats, understanding Hawaiian coot and gallinule movements, population abundance, and factors affecting nesting is critical to their conservation.
Keywords: Hawaiian waterbirds; movement ecology; waterbird conservation; home range; climate change; nest site selection